2008
DOI: 10.1111/j.1479-828x.2008.00868.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of violence against pregnant women in Abeokuta, Nigeria

Abstract: Gender-based violence is common in our environment. Health-care providers should routinely screen for gender-based violence during antenatal visits in order to protect the health of both mother and child.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
80
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 26 publications
17
80
4
Order By: Relevance
“…The explanation for this is when pregnancy is unplanned, conflict may be raised between couples and violence may be followed based on this conflict. In contrary to current study, study done in Nigeria and South Africa did not found significant association with experiencing violence and unplanned pregnancy [12] [13]. This may be due to they recruited the women who had made at least one previous visit to the antenatal clinic, because of this women who had unplanned pregnancy and abused may not participate in the study.…”
Section: Discussioncontrasting
confidence: 44%
“…The explanation for this is when pregnancy is unplanned, conflict may be raised between couples and violence may be followed based on this conflict. In contrary to current study, study done in Nigeria and South Africa did not found significant association with experiencing violence and unplanned pregnancy [12] [13]. This may be due to they recruited the women who had made at least one previous visit to the antenatal clinic, because of this women who had unplanned pregnancy and abused may not participate in the study.…”
Section: Discussioncontrasting
confidence: 44%
“…Information about gender-based violence against women from low-income countries is scarce and may be under reported [6,7]. The aim of the present study was to explore the relationship between domestic violence in the period before pregnancy and the pattern during the pregnancy and in the postpartum period.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from a Nigerian study carried out in the southwest documented a prevalence of 47.1% among pregnant women examined with 11.7% occurring in their current state of pregnancy (Ezechi et al, 2004). A later study carried in the same region of the country reported a 14.2% prevalence of violence among pregnant women attending antenatal services twelve months prior to current pregnancy and 2.3% reported violence in current pregnancy (Fawole et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the exact relationship between alcohol and violence remains unclear, researches have consistently found drinking patterns to be related to intimate partner and sexual violence. Fawole et al (2008) reported that low level of education in both woman and partner and consumption of alcohol by partners were significant risk factors for violence. This was confirmed by this study as 95% of respondents married to partners who take alcohol had ever experienced a form of violence or the other.…”
Section: Help Seeking Pattern After Experiencing Violence and Coping mentioning
confidence: 99%